Technology as a Source of Language Input and Practice and its Influence on the Vocabulary Development of University EFL Students - Adela Talbi Hassani (International Association of Online Engineering (IAOE), 2021)
This paper addresses the extent to which technology-based language resources and tools influence the vocabulary development among University students learning English as a foreign language (EFL). The vocabulary development of 184 undergraduate students at the University of xxxxxxxx (xxxxxxx) is studied in terms of the growth of their receptive vocabulary size as well as their use of vocabulary learning strategies (VLS) across three years, and any possible correlation between this development and the use of technology is analysed. Findings reveal that for the majority of the population, the highly frequent use of multimedia tools was largely confirmed; however, for most students there was no significant correlation between the use of such resources and the growth pattern of their vocabulary knowledge. Only the low-intermediate students who had just joined the university were the exception, as their use of Internet to search for information or to communicate with others seemed to be significantly correlated to their vocabulary development. These findings have interesting implications for the classroom as they show the high potential of technology-based resources in developing vocabulary especially in environments in which English is taught as a foreign language (FL), and used only in classroom contexts. Learners appear to be "connected" enough and avid of technology based tools; however, they seem to need assistance from instructors to maximize the positive support of such tools on their language learning in general and vocabulary development in particular.